Effectiveness of an online asthma education program in adults with asthma in general practice: Results from a cluster randomised controlled trial - Eck, Stefanie; Baumgärtel, Andrea; Hapfelmeier, Alexander; Linde, Klaus; Sanftenberg, Linda; Stark, Stefanie; Schultz, Konrad; McClatchey, Kirstie; Pinnock, Hilary; Schneider, Antonius (Respiratory Medicine, 2025)
Background: Asthma education programs (AEPs) are crucial to improving patient outcomes, but few patients participate. Therefore, an online asthma education program (electronic AEP, eAEP) has been developed. We aimed to investigate the effectiveness of the eAEP in adults with asthma in terms of asthma knowledge, symptom control and emergency treatments. Methods: In a cluster randomised controlled trial, general practitioner (GP) practices were randomly assigned to either access to the intervention (eAEP), or usual care (UC) control. Outcomes were assessed at baseline, two weeks, three and six months. Primary endpoint was the difference in Asthma Knowledge Test (AKT) scores after completion of the eAEP/UC. Secondary outcomes included symptom control (Asthma Control Test, ACT) and emergency treatments. Findings: 62 patients from 10 intervention practices and 46 patients from 11 control practices were analysed. The intervention group had significantly greater improvements in mean AKT scores (between-group adjusted mean difference (AMD), 9.3 (95 % CI 6.3–12.3), p < 0.001) at the primary endpoint. Differences remained relatively stable during the six-month follow-up. Between-group AMD in the ACT was 1.4 (95 % CI -0.1-2.8, p < 0.062) three months after the eAEP/UC and 1.6 (95 % CI 0.2–2.9, p < 0.023) at study end. More intervention group patients demonstrated the inhalation technique correctly (98 % vs. 79 %, p = 0.007), received peak expiratory flow instructions (94 % vs. 32 %, p < 0.001) and an asthma action plan (96 % vs. 50 %, p < 0.001). Interpretation: The eAEP was effective in improving knowledge over six months and showed beneficial effects on symptom control. The eAEP may contribute to improved asthma care in GP settings.
CRIS-Team Scopus Importer:2025-04-01
Keywords: Asthma; Asthma knowledge; Asthma self-management; Digital intervention; Primary care; Symptom control